The Combination of Entomopathogenic Fungus of Beauveria bassiana (Balls) Vuill. with the Insect Growth Regulator (IGR) of Lufenuron Against Reproductive of Bactrocera carambolae Fruit Flies (Diptera: Tephritidae) - Adrianto Marthinus Ndii; Bambang Tri Rahardjo; Toto Himawan (Journal of Experimental Life Science)
The study aimed to determine the reproductive ability of fruit flies B. carambolae treated with B. bassiana and Lufenuron. This study is conducted at the Laboratory of Pest. Department of Plant Pests and Diseases, Faculty of Agriculture, University of Brawijaya, Malang. This study used a completely randomized design with nine treatment and three replications. The study was trying to evaluate the effect of B. bassiana and Lufenuron on the reproduction capacity of B. carambolae. Results showed that adults of B. carambolae to applied combination of B. bassiana and Lufenuron immediately after coming out of the pupae until day eighth have the average number of eggs laid is 7.69%, a decrease of fecundity 92.40%, egg fertility by 61.38% and 95.24% decrease of reproduction. Adults of B. carambolae applied of B. bassiana and Lufenuron on day eighth until day sixteenth (for 8 days), show a decrease in the number of eggs laid by 13.63%, the decrease of fecundity 88.50%, egg fertility by 50.16% and decrease of reproduction by 93.12%.